Evaluation of a newly discovered breast cancer susceptibility locus at 6q25.1 in Iranian Azari-Turkish women - Garehdaghchi, Ziba; Derakhshan, Siam Mansoori; Khaniani, Mahmoud Shekari (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study: A recent breast cancer genome-wide association study (GWAS) identified single-nucleotide polymorphism (SNP) rs2046210 on 6q25.1 showing a strong association with breast cancer risk. Numerous association studies have been conducted to investigate the relationship between this polymorphism and breast cancer risk in various populations. There have been conflicting reports about the association of this locus with breast cancer risk in different ethnic groups. For the first time, this study has investigated the association of rs2046210 SNP with breast cancer risk in Iranian Azari-Turkish women in North West Iran. Material and methods : In this study 192 breast cancer subjects and 186 healthy controls were genotyped using Taqman SNP genotyping assays for different SNP rs2046210 alleles. Results : No significant association between rs2046210 SNP alleles and the risk of breast cancer was detected in Iranian Azari-Turkish women. Conclusions : The data suggests that rs2046210SNP does not play a role in the aetiology of breast cancer in the Iranian Azari-Turkish population, and it indicates possible genetic differences for breast cancer between different population ancestries. Our result is an important contribution to the literature about genetic susceptibility for breast cancer in Asian populations. Additional studies are required to confirm our findings.